Current 3R practices on construction waste minimization in construction site - Mohamad Zain Hashim,; Idris Osman,; Siti Hafizan Hassan,; Muriatul Khusmah Musa, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rise of the construction industry nowadays has a lot to do with the production of industrial waste. The needs of the construction industry whether for developing countries or developed countries is something that cannot be avoided. The main objectives were to find the main causes of construction waste generation, assess the level of awareness of 3R concepts and to evaluate the current approach used at the construction site in reducing construction waste. The study involves companies involved in the construction industry, namely architects, consultants and contractors. The research method used is a questionnaire to the construction industry. Results show that most respondents are aware of the benefits of 3R practices but most of them also do not practice the 3R due to lack of knowledge. The finding of this research is the construction waste can be reducing after practising the 3R.